Locus of control, savings and propensity to save - Alessandro Bucciol; Serena Trucchi (Cardiff University, Cardiff Business School, 2020)
We study the relationship between saving choices and a key psychological characteristic such as locus of control using data from a longitudinal survey representative of the Dutch population. Locus of control measures the extent to which individuals perceive their life outcomes to be determined by their own actions, as opposed to external factors. Our findings show that those who believe to be in control of future outcomes save more, both at the extensive(probability to save) and intensive margins (amount of savings). We also investigate the mechanisms behind the relationship. Locus of control may affect both the propensity to save for general purposes and savings to achieve a specific purchase goal (e.g.buying a house). We find that both channels are significant, the latter being more sizeable.
Keywords: D14; D91; 330; Locus of Control; Saving decisions; Propensity to save; Mediation analysis